2016
DOI: 10.1177/1753465816645478
|View full text |Cite
|
Sign up to set email alerts
|

Emergency management for congenital tracheal stenosis with endoluminal stenting in pediatric intensive care units

Abstract: Objective: The objective of this study was to share our experience in the management of congenital tracheal stenosis (CTS) using self-expanding intraluminal stents in infants. Methods: From January 2010 to August 2012, 31 infants with CTS treated using stents by bronchoscope in pediatric intensive care units (PICUs) were recruited for this study. Results: Among the 31 patients, 17 were male and 14 were female with their ages ranging from 55 days to 22 months. CTS was associated with congenital heart disease (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Two series with five patients each reported the long-term outcome of stents used in tracheal stenosis after endoscopic dilation, with good functional outcomes, but a high complication rate [103,134]. Another case series reported on rapamycin-eluting stents after balloon dilation of congenital tracheal stenosis in eight infants, but with only a short follow-up [135]. A retrospective study of 21 severely sick patients in whom stenting was used as the last resort reported clinical improvement in 18 (85%) patients with complications requiring endoscopic treatment or removal of the stent in five (27%) of them; stent related mortality was 4% [136].…”
Section: Airway Stentsmentioning
confidence: 99%
“…Two series with five patients each reported the long-term outcome of stents used in tracheal stenosis after endoscopic dilation, with good functional outcomes, but a high complication rate [103,134]. Another case series reported on rapamycin-eluting stents after balloon dilation of congenital tracheal stenosis in eight infants, but with only a short follow-up [135]. A retrospective study of 21 severely sick patients in whom stenting was used as the last resort reported clinical improvement in 18 (85%) patients with complications requiring endoscopic treatment or removal of the stent in five (27%) of them; stent related mortality was 4% [136].…”
Section: Airway Stentsmentioning
confidence: 99%
“…Cryotherapy has been used for restoration of airway patency in different conditions including traumatic tracheal stenosis [12], endobronchial casts or mucus plugs [13], removal of foreign bodies [7] and the recanalization of obstructed bronchial stents [14].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple stents can be removed in batches so as to avoid excessive damage to the airway that may occur when multiple stents are removed all at once. After the stent is removed, the wound can be treated with CO 2 cryotherapy to reduce the rate of granulation tissue hyperplasia (12).…”
Section: Discussionmentioning
confidence: 99%